Strengthening Corporate Zakat Policy in Indonesia - Andriani, Andriani; Mairijani, Mairijani (IQTISHADIA, 2019)
Zakat is one of five pillars in Islam. As the biggest Moslem population country, Indonesia should considered zakat as potential instrument to reduce poverty. In normal economics situation where most growing entities generate profit yearly, business zakat plays an important role to create value added for prosperity. However the regulation of business zakat in Indonesia is very lack. Regulation of Zakat relies solely on Zakat act No.23 year 2011 that doesn’t cover the issue of business zakat. Another regulatory body is the Indonesian Accounting Institution that established sharia accounting standard, namely PSAK 101 which obliges sharia entities to provide business zakat report. Furthermore, the Indonesia Stock Exchange has launched Indonesia Sharia Stock Index (ISSI) and Jakarta Islamic Index (JII) for entities that trade sharia stocks in the capital market. The aim of the research is to discuss the form of policies to support business zakat application in Indonesia. Literature survey is mainly used as methodological approach to conduct this research. Fiqh literatures and sharia accounting standard are explored to support regulation of business zakat in Indonesia. Policies by regulatory bodies with regard to business zakat are also dicussed in order to support business zakat implementation in Indonesia. Empirical data from corporates that are indexed by ISSI or JII in Indonesia Stock Exchange are collected to provide the potency of business zakat. This paper initiates policies to be applied in supporting business zakat implementation in Indonesia.